2012
DOI: 10.3390/molecules17078206
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Synthesis of 3′,4′-Diaminoflavones to Evaluate Their Antioxidant Ability and Cell Apoptosis of Zebrafish Larvae

Abstract: We described herein a concise synthesis of 3′,4′-diaminoflavone 10. This new, three-step synthetic approach is more efficient than the conventional seven-step synthetic method. The route is shortened significantly by introducing the amino moieties early and eliminating the need for nitro group reduction. The other two analogues, 5,7-dihydroxy-3′,4′-diaminoflavone 11 and 5,7-dimethoxy-3′,4′-diaminoflavone 12, were also synthesized similarly. The above three compounds, along with flavone, were evaluated for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that UV exposure is associated with the generation of ROS 20 , 27 . In this study, we detected the level of ROS in zebrafish embryos treated with UV and 50–100 ppm of comfrey leave extracts.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have shown that UV exposure is associated with the generation of ROS 20 , 27 . In this study, we detected the level of ROS in zebrafish embryos treated with UV and 50–100 ppm of comfrey leave extracts.…”
Section: Resultsmentioning
confidence: 98%
“…Using commercially available acyl chlorides, the esterification occurs simply in dry pyridine 101,[121][122][123][124][125][126][127] or in the presence of potassium carbonate as base and acetone as solvent. 128,129 Otherwise, acyl chlorides can be prepared in situ by treatment of the corresponding carboxylic acids with phosphoryl chloride in dry pyridine ranging from 0 °C130-132 to room temperature [133][134][135][136][137] and even at 80 °C138 ; with thionyl chloride and pyridine in dichloromethane 139 or DMF 140 ; with 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDCI) and 4-dimethylaminopyridine (DMAP) using DMSO, 141 triethylamine 142 or dichloromethane [143][144][145] as solvents; with N,N-dicyclohexylcarbodiimide (DCC) and DMAP in dichloromethane at room temperature 139,146 ; and with DCC in the presence of a catalytic amount of 4-pyrrolidinopyridine (4-PPy) in dichloromethane at room temperature. 136 The second step, known as Baker-Venkataraman rearrangement, involves the transposition of the acyl group from the C-2 0 to C-2 of the acetophenone moiety to give the corresponding 1-(2-hydroxyaryl)propane-1,3-diones (in equilibrium with the respective enolic form).…”
Section: Through Baker-venkataraman Rearrangementmentioning
confidence: 99%
“…136 The second step, known as Baker-Venkataraman rearrangement, involves the transposition of the acyl group from the C-2 0 to C-2 of the acetophenone moiety to give the corresponding 1-(2-hydroxyaryl)propane-1,3-diones (in equilibrium with the respective enolic form). The reaction takes place in the presence of potassium hydroxide with pyridine [121][122][123][125][126][127][128][130][131][132][133][134]137,[140][141][142]145,146 or DMSO 133,136,138 as solvent; or under less conventional conditions such as of sodium hydride in THF at reflux, 101,124 potassium t-butoxide in THF at room temperature, 139,143 sodium hydroxide in DMSO at 60 °C143 or MgBr 2 ÁEt 2 O and N,N-diisopropylethylamine (DIPEA) in dichloromethane at room temperature. 127,147 Finally, cyclodehydration of the 1,3-diketones formed provides the desired 2-substituted chromones.…”
Section: Through Baker-venkataraman Rearrangementmentioning
confidence: 99%
“…Moreover, other studies have utilized zebrafish model to explore the bioactivity of antioxidants. For example, Shih et al (2012) demonstrated the potent antioxidant effect of 3′,4′-diaminoflavones using zebrafish larvae and Chen et al (2012) also used this model to evaluate the antioxidant effect of several flavonoids. Furthermore, the antioxidant activity of bioactives was determined by monitoring oxidative stress-induced cell death in a zebrafish model.…”
Section: Zebrafish Modelmentioning
confidence: 99%
“…Furthermore, the antioxidant activity of bioactives was determined by monitoring oxidative stress-induced cell death in a zebrafish model. Yang et al (2012) and Shih et al (2012) counted stressinduced cell death in zebrafish model to evaluate the antioxidant potential of quercitrin and 3′,4′-diaminoflavones.…”
Section: Zebrafish Modelmentioning
confidence: 99%